Consumer Preference of Broiler Meat Attributes in Traditional Markets - Hamdi Mayulu; Arif Rahman; Roosena Yusuf (Hasanuddin Journal of Animal Science (HAJAS), 2019)
Meat needs (Broilers) have increased and meat consumption is influenced by consumer preferences caused by shifting consumption patterns, and is supported by low prices compared to beef.  The shift is influenced by prices, substitute goods, tastes, season, age, education, number of dependents, income, and increasing population so that preferences, and attributes that consumers consider in buying broiler meat in traditional markets need to be studied.  The study used a purposive sampling method, with the criteria of the Adji Dilayas Sanggam Market,  Senja Market, and the Milono Market in Berau Regency, having broiler meat traders.  Determination of respondents using proportional sampling techniques, each market 12 respondents (36 respondents), meet the smallest number of traders considered to meet the minimum sample criteria.  Sources of data obtained from primary data and secondary data.  The results showed that broiler meat that has a golden color, clean skin, medium carcass size, physically not bruised, fresh meat, and especially the chest.  Chi Square analysis showed that all attributes were significantly different (p <0.05), meaning that there were differences in preferences for the attributes of broiler meat in traditional markets.  Fishbein Multiatribute Analysis proves that meat freshness, flesh color, carcass physicality, skin cleanliness, carcass size, and carcass portion are the most considered, and or not considered attributes.